The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.36227/techrxiv.12933071.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of sector coupling in the green transition: A least-cost energy system development in North Europe towards 2050

Abstract: <div>This paper analyses the role of sector coupling towards 2050 in the energy system of North Europe when pursuing the green transition. Impacts of restricted onshore wind potential and transmission expansion are considered. Optimisation of the capacity development and operation of the energy system towards 2050 is performed with the energy system model Balmorel. Generation, storage, transmission expansion, district heating, carbon capture and storage, and synthetic gas units compete with each other. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Particularly, offshore grid modelling and data is explained in detail in section 2.1.3. A few updates to the data used in [7] have been made in this paper and are mentioned along this section.…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, offshore grid modelling and data is explained in detail in section 2.1.3. A few updates to the data used in [7] have been made in this paper and are mentioned along this section.…”
Section: Methodology and Datamentioning
confidence: 99%
“…The European Commission is already prioritizing the development of a North Sea offshore grid [9], for it to contribute to achieving the European Union goals for 2030 and 2050 [10]. Gea-Bermúdez et al [7] investigated the influence of the grid architecture and planning horizon on the North Sea offshore grid, finding that offshore grids reduce system costs and that long-term planning is crucial to reduce costs and increase the integration of VRE, especially offshore wind. Konstantelos et al [11] also found that integrated offshore grids provide substantial net benefit over non-integrated networks.…”
Section: Introductionmentioning
confidence: 99%
“…These inputs include the cost of energy technologies, CO 2 taxes, fuel prices, future energy demand, and fuel potentials. An overview of the model and data used in this paper can be found here [31], although a few updates have been made for the purpose this paper, the main addition being the addition of six conventional onshore wind turbines and the LW turbines. Other data updates include energy efficiency assumptions and updated national onshore wind potentials.…”
Section: Input Data For Energy System Modelmentioning
confidence: 99%
“…The optimisations and simulations, except for the VRE simulations, are performed with the energy system model Balmorel [24], an energy system tool, deterministic, open source [25], with a bottom-up approach. It has been traditionally used to model the electricity and district heating sectors, although it is being developed to increase its capabilities and include more sectors [26].…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…Both of these aspects can be highly relevant for the correct operation of the system, especially towards 2050 with more VRE penetration. Furthermore, future research should also include stronger sector coupling, since it can influence considerably the generation of VRE technologies and the need for flexibility ([33], [23], [26]) .…”
Section: Limitations Of the Studymentioning
confidence: 99%